Main Priorities of Development of Canning Industry in Azerbaijan - Abbasov, V.; Shukurova, S. (Економічний вісник Донбасу, 2022)
The article discusses the role and importance of foreign trade relations in the development of the canning industry in Azerbaijan and the main priorities for its development, applies the method of comparative analysis of the production, import and export potential of canned fruit and vegetables and canned juices, considers arrangements for the implementation of the main directions taken in this area, as well as the share of individual countries in the export of local products, in accordance with the procedure for conducting a regulatory impact assessment in relation to the studying issues. At the same time, the activity of a more efficient agrarian market for the country is studied in order to form the export potential of canning industry products, to create more significant areas for the import-export of canning production, and the studies are carried out to ensure the formation and efficiency of the import-export system. У статті розглядається роль і значення зовнішньоторговельних зв’язків у розвитку консервної промисловості в Азербайджані та основні пріоритети її розвитку, застосовано метод порівняльного аналізу виробництва, імпорту та експорту потенціалу плодоовочевих консервів та консервованих соків, розглядаються заходи щодо реалізації основних напрямків у цій сфері, а також частки окремих країн в експорті вітчизняної продукції відповідно до порядку проведення оцінки регуляторного впливу щодо питань, що вивчаються. Водночас досліджується діяльність більш ефективного аграрного ринку країни з метою формування експортного потенціалу продукції консервної промисловості, створення більш значущих площ для імпорту-експорту консервної продукції, а також проведено дослідження щодо забезпечення формування та ефективності системи імпорту-експорту.